A community-based non-randomised controlled intervention programme for blood pressure control in China. (December 2017) - Wang, Mengying; Wu, Tao; Hu, Yonghua; Cao, Weihua; Zhan, Siyan; Lv, Jun; Gao, Wenjing; Yu, Canqing; Wang, Shengfeng; Wang, Geng; Wang, Jin; Dai, Liqiang; et al.
Abstract: Background: The benefits of community-based interventions for blood pressure control are well established. However, whether their effects differ by presence of common chronic diseases is unclear. We aimed to explore the influence of diabetes history and baseline blood pressure using data from a community-based intervention programme in Shanghai, China. Methods: A non-randomised, controlled, intervention programme from Jan 1, 2008, to Dec 31, 2010, was conducted in two communities in Shanghai. Comprehensive interventions including health education, lifestyle interventions, and antihypertensive treatment were offered to participants in the intervention community. We adopted propensity-score analysis to adjust the imbalance of baseline characteristics including sex, age, education level, smoking, alcohol consumption, salt intake, physical activity levels, family history of hypertension, body-mass index, and central obesity between the two communities to evaluate the net effect of the intervention through comparing the changes in systolic blood pressure between the intervention and control communities. Findings: 16 389 participants (7563 residents from the intervention community and 8826 residents in the control community) participating in both baseline and outcome surveys were included in the analysis. We found the intervention effect to be broadly similar by baseline diabetes history. The net decline in systolic blood pressure was 1·02 mm Hg (95% CI −1·91 to −0·14, p=0·02) for patients with diabetes at baseline and 0·74 mm Hg (95% CI −0·98 to −0·50, p<0·0001) for participants without diabetes at baseline in the intervention community when compared with the control community after propensity score adjustment. Moreover, when we stratified 1749 patients who had hypertension at baseline without taking antihypertensive medicine into four strata (systolic blood pressure <130 mm Hg, 130–139 mm Hg, 140–159 mm Hg, and ≥160 mm Hg), we noted a significant net adjusted reduction in systolic blood pressure among participants with the lowest systolic blood pressure at baseline in the intervention community compared with those in the control community (−2·13 mm Hg, p=0·007). Interpretation: The study intervention was more effective among patients with hypertension whose systolic blood pressure was less than 130 mm Hg without taking medicine at baseline, but we failed to detect any difference by presence of diabetes. The findings demonstrate the importance of developing better intervention strategies to control blood pressure based on baseline levels in patients with hypertension. Funding: National Science and Technology Support Projects for the "Eleventh Five-Year Plan" of China (number 2006BA101A01).